HAND PUPPET: A TEACHING – LEARNING STORYTELLING MEDIA - M. Nur Hakim; Zuriyati; Saifur Rohman (Getsempena English Education Journal, 2019)
The media has an important role in learning activities to be able to arouse interest, motivation, and provide stimulation to increase students learning activities. The benefit of the media in the learning process is facilitating interactions between the teacher and students, so that the learning will be more effective and efficient. Generally, the purpose of this study describes the process of applying hand puppet media to improve students’ skills in storytelling. This study uses the design of the Kemmis and McTaggart model which includes the stages of planning, action, observation, and reflection. The technique used in collecting data is through observation and interviews, while the data analysis is done by descriptive qualitative. The findings of this study reveal an increasing in the students’ ability in storytelling for each cycle which is characterized by self-confidence, the ability to master the story, and mastery of expression. The use of hand puppets as a tool in storytelling activities can be communicative interactions and creative ideas, so that the students can focus on storytelling well. Thus, it can be concluded that hand puppets can help students improve their storytelling abilities.